Accounting Conservatism, Information Asymmetry and Cash Holdings - Walid Shehata; Ahmed Rashed (STIE Malangkucecwara, 2021)
This paper focuses on explore the association between accounting conservatism and cash holding through a mediating effect of information asymmetry (IA) for Egyptian firms listed in EGX 100 within the period between 2013 -2018 through 124 firms with 703 firm-observations. The results indicates that (1) conservatism doesn’t have an enormous effect on information asymmetry, (2) information asymmetry doesn’t have a serious effect on cash holding, (3) there’s not any mediation role of information asymmetry within the relationship between conservatism and cash, (4) conservatism effect a negatively on cash holding